HIV may indirectly accelerate coronary artery disease through enhancing the effects of conventional and non-conventional cardiovascular risk factors. (25th November 2020) - Kolossvary, M; Fishman, E.K; Gerstenblith, G; Bluemke, D.A; Mandler, R.N; Kickler, T.S; Bazr, S; Chen, S; Lai, S; Lai, H
Abstract: Background/Introduction: Cross-sectional studies are inconsistent on the potential independent adverse effects of human immunodeficiency virus (HIV)-infection on coronary artery disease (CAD). Furthermore, there is no information on the potential effects of HIV-infection on plaque volumes. Also, only the independent effects of HIV-infection on CAD have been investigated. Purpose: In a prospective longitudinal observational cohort, we wished to assess whether HIV-infection accelerates CAD independently, or by acting in synergistic fashion with conventional and nonconventional cardiovascular risk factors to accelerate disease progression as assessed by clinical and volumetric parameters of CAD on coronary CT angiography (CCTA). Methods: Overall, 300 asymptomatic individuals without cardiovascular symptoms but with CCTA-confirmed coronary plaques (210 males, age: 48.0±7.2 years) with or without HIV (226 HIV-infected) prospectively underwent CCTA at two time points (mean follow-up: 4.0±2.3 years). Agatston-score, number of coronary plaques, segment stenosis score were calculated, and we also segmented the coronary plaques to enumerate total, noncalcified (−100–350HU) and calcified (≥351HU) plaque volumes. Linear mixed models were used to assess the effects of HIV-infection, atherosclerotic cardiovascular disease (ASCVD) risk, years of cocaine use and high-sensitivity C-reactive protein on CCTA markers of CAD. Results: In univariate analysis, there was no significant difference in CAD characteristics between HIV-infected and -uninfected, neither at baseline nor at follow-up (p>0.05 for all). Furthermore, there was no significant difference in annual progression rates between the two groups (p>0.05 for all). By multivariate analysis, HIV was not associated with any CAD parameter (p>0.05 for all). However, among HIV-infected individuals, each year of cocaine use significantly increased all CAD parameters (p<0.05 for all), while ASCVD risk score was significantly associated with CAD parameters except for Agatston-score (p<0.05). These associations were only present among HIV-infected individuals. Conclusion(s): Instead of directly worsening CAD, HIV may promote CAD through increased susceptibility to conventional and nonconventional cardiovascular risk factors. Therefore, aggressive management of both conventional and nonconventional cardiovascular risk factors is needed to reduce cardiovascular burden of HIV-infection. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): National Institutes of Health, National Institute on Drug Abuse